Anomalous X-ray diffraction studies of ion transport in K+ channels. Issue 1 (December 2018) - Langan, Patricia; Vandavasi, Venu; Weiss, Kevin; Afonine, Pavel; el Omari, Kamel; Duman, Ramona; Wagner, Armin; Coates, Leighton
Abstract Potassium ion channels utilize a highly selective filter to rapidly transport K+ ions across cellular membranes. This selectivity filter is composed of four binding sites which display almost equal electron density in crystal structures with high potassium ion concentrations. This electron density can be interpreted to reflect a superposition of alternating potassium ion and water occupied states or as adjacent potassium ions. Here, we use single wavelength anomalous dispersion (SAD) X-ray diffraction data collected near the potassium absorption edge to show experimentally that all ion binding sites within the selectivity filter are fully occupied by K+ ions. These data support the hypothesis that potassium ion transport occurs by direct Coulomb knock-on, and provide an example of solving the phase problem by K-SAD. The number of K+ occupied binding sites in the selectivity filter of potassium ion channels is still under debate. Here, the authors collect diffraction data on the K+ selective NaK channel NaK2K at a wavelength of 3.35 Å, close to the K absorption edge, revealing that all four binding sites in the selectivity filter are fully occupied by K+ ions.